A genealogical analysis of the deployment of personality disorder in the UK psychiatric context since 1950: corpus linguistics as an adjunct to a Foucauldian discourse analysis of diachronic corpora of psychiatric texts from 1950 to 2007 - Parnell, Mike (2010)
In order to examine how personality disorder and related concepts have been deployed in UK psychiatric literature over the last 50 years, a number of methodological and theoretical approaches are initially examined. It is concluded that a Foucauldian discourse analytic approach, supported and informed by findings from Corpus Linguistic techniques would provide a means of uncovering discourses surrounding the use of personality disorder in such literature. A new combined methodology is proposed that uses evidence from a Corpus Linguistic analysis to support Willig's six step methodology for Foucauldian Discourse Analysis (Willig 2001b). Three diachronic corpora of UK psychiatric articles are created, covering the 1950s, 1970s and 2000s. These are interrogated using word frequencies, concordance and collocational approaches in order to uncover patterns which reflect discourse changes over these periods.